2018
DOI: 10.1111/jfs.12444
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological safety and quality of Italian donkey milk

Abstract: Considering that few data are currently available about donkey milk microbiological quality and given the spread of food-borne outbreaks strongly linked with the consumption of raw milk, the aim of the present study was to investigate the microbiological quality and the food safety of Italian donkey milk. Total viable count (TVC) and coagulase-positive Staphylococcus were evaluated to verify the process hygiene criteria for donkey's milk. The presence of Salmonella spp., Listeria monocytogenes, Cronobacter sak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…CM (4,0) was found to be the most delicious beverage which is followed by DM (3,7), CMK (2,3), and DMK (1,5). It was found that DM had the best odour (3,6) among all samples and with fermentation the odour of the kefir samples was described as more obnoxious. As overall assessment participants found milks more delicious than kefirs.…”
Section: Sensory Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…CM (4,0) was found to be the most delicious beverage which is followed by DM (3,7), CMK (2,3), and DMK (1,5). It was found that DM had the best odour (3,6) among all samples and with fermentation the odour of the kefir samples was described as more obnoxious. As overall assessment participants found milks more delicious than kefirs.…”
Section: Sensory Analysismentioning
confidence: 97%
“…Milk is an important element in human diet since its unique components which promote nutritional, immunological, and developmental requirements of young mammals [1]. As a result of the intolerance and allergic reactions due to consumption of cow's milk (CM) by people, there has been an emerging need for alternative milk sources like horse and donkey milk (DM) in recent years [2] and DM is defined as "pharmafood" which is highly preferred by the consumers [3]. Nowadays, the economic value of DM has been noticed not only for its nutritional value but also for its therapeutic and functional properties due to likeliness of its chemical composition to human milk, especially for infants who have cow's milk protein allergy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Also, donkey milk is characterized by a low somatic cell count, with an average value around 35 × 1000 mL −1 [ 47 , 48 , 49 ]. As to the total bacterial count, the literature data indicate values ranging from 7 cfu mL −1 to 90,000 cfu mL −1 , both for horse and donkey milk ( Table 2 ), and it is generally considered that they do not frequently harbor foodborne pathogens due to antimicrobial properties connected to substances such as lactoferrrin, lysozyme, immunoglobulins, and lactoperoxidase [ 34 , 50 , 51 , 52 , 53 , 54 ]. However, hygienic issues have sometimes been reported [ 53 ].…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…In a survey of 90 samples of donkey milk, two samples contained two main food-borne pathogens of growing importance for human health: one sample harbored Escherichia coli O157 producing the Shiga-like-toxin (SLT-I and SLT-II), and the other one contained Campylobacter coli . The study demonstrated that raw donkey milk might represent a realistic health risk for consumers, and, as for raw cow milk, specific microbiological parameters and criteria need to be established for authorized dairy donkey farms [ 50 ]. The effectiveness of in-vat pasteurization at +65 °C for 30 min and storage at refrigeration (+3 °C ± 2 °C) and freezing temperatures (−20 °C ± 5 °C) on some hygienic characteristics of donkey milk was investigated.…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…Mottola et al [29] showed that out of 90 samples of donkey milk, one (1.11%) contained E. coli O157 harboring the Shiga-like- toxins (SLT-I and SLT-II); in one sample (1.11%) Campylobacter (C.) coli was recovered. The authors stated that the isolation of C. coli and E. coli O157 in donkey milk aroused a great public health issue.…”
Section: Microbiological Hazardsmentioning
confidence: 99%